AirTemperature: Extensible Software Library to Generate Air Temperature Data. (6th April 2010) - Donatelli, Marcello; Bellocchi, Gianni; Habyarimana, Ephrem; Bregaglio, Simone; Baruth, Bettina
Abstract : The development of a set of reusable libraries to support custom applications has become a goal in biophysical modeling projects. This is true for weather modeling as well. AirTemperature is a software component providing a collection of deterministic and stochastic approaches to generate atmospheric temperature data on daily and hourly time steps. Data generated on a daily time step consist of maximum and minimum air temperature and dew point temperature. Hourly estimations include air and dew point temperatures. The software design allows for extension of the models implemented without recompiling the component. The component, inclusive of hypertext help documentation files, is released as compiled .NET2 version, allowing application development in either programming environment. A sample client and a sample extension project using AirTemperature are provided as source code. A sample Web service and a Web application are also developed as examples of possible use of the component.